INTERVENSI KEMANUSIAAN DARI AMNESTY INTERNATIONAL TERHADAP ISU DISKRIMINASI HAM UNTUK FIRST NATION DI KANADA PASCA 2016 - Sandiwan Putra Bintang Anugrah (JOURNAL OF LAW AND NATION, 2026)
My research examines Amnesty International's intervention in the issue of discrimination against First Nations in Canada. The discussion is written in a descriptive, argumentative, and analytical manner using qualitative research methods with secondary data. The results of the study show that Amnesty's efforts have not been successful in resolving this issue. Using the English School Theory, which focuses on pluralism and solidarism, this theory finds the reason for the obstacles to Amnesty's dialogue with the Canadian government regarding indigenous rights violations to be the different framing of First Nation issues. Amnesty's strategy consists of three approaches: first, publishing research, petitions, and posters with the assistance of other mass media; second, correspondence with the government; and third, collaboration with activist organisations.